Penerapan Media Flashfast Flipbook Berbasis Problem Based Learning dalam Peningkatan Hasil Belajar Materi Uang Siswa Kelas IV - Wahani, Namira; Purwati, Panca Dewi (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research is motivated by the problems experienced by teachers in teaching Natural and Social Sciences (IPAS), namely that teachers have difficulty presenting interesting media to students. The aim of this research is to describe the application of flashfast media assisted by flipbooks based on the problem based learning model on money for class IV students and to describe the effectiveness of flashfast media assisted by flipbooks based on the problem based learning model on money in improving student learning outcomes. The subjects in the research were 20 grade IV students at SD Negeri Karanganyar 1 Semarang City. Data analysis techniques used include tests, interviews, observation and documentation. Data analysis uses qualitative descriptive analysis. The results of the research show that the application of flashfast media assisted by flipbooks based on the problem based learning model of money material for class IV students at SDN Karanganyar 1 Semarang city is effectively used in learning money material as seen by an increase in the completeness of student learning outcomes in the pretest and posttest by 45%.